2023
DOI: 10.3390/jcm12093119
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Cognitive Impairment in Hemodialysis Patients and Related Factors including Depression and Anxiety

Abstract: Introduction: Hemodialysis patients are at higher risk of developing cognitive impairment, but the pattern of affected cognitive domains is still undetermined. Little is also known about the symptoms of depression and anxiety in hemodialysis patients. Methods: In this cross-sectional study, we included 74 consecutive adult patients undergoing hemodialysis. Cognitive functions were assessed using the Addenbrooke Cognitive Test III. In addition, all patients were screened for symptoms of depression and anxiety u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…patients with ESKD demonstrated problems in tests assessing executive function in the first months of RRT, while there were no difficulties in general cognitive skills [ 27 ]. Furthermore, a few studies, assessing cognitive abilities in CKD patients, including our previously published study, found verbal fluency to be the most affected domain, which reflects executive dysfunction [ 3 , 4 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…patients with ESKD demonstrated problems in tests assessing executive function in the first months of RRT, while there were no difficulties in general cognitive skills [ 27 ]. Furthermore, a few studies, assessing cognitive abilities in CKD patients, including our previously published study, found verbal fluency to be the most affected domain, which reflects executive dysfunction [ 3 , 4 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplantation (KT) is the treatment of choice for most patients with end-stage kidney disease to increase survival and quality of life [ 1 ]. Cognitive impairment (CI) is common in hemodialysis and peritoneal dialysis patients [ 2 , 3 ] and may also be detected in kidney transplant candidates [ 4 ]. CI prior to KT is associated with a lower likelihood of being listed for transplant and with a longer waitlist for transplantation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%